1994
DOI: 10.1139/x94-082
|View full text |Cite
|
Sign up to set email alerts
|

Fall lifting and long-term freezer storage of ponderosa pine seedlings: effects on starch, root growth, and field performance

Abstract: To determine the response of seedlings lifted in fall and stored at temperatures below 0 °C until outplanting, ponderosa pine (Pinusponderosa Dougl. ex Laws.) seedlings from two Oregon seed sources were harvested in September, October, and November (stored below 0 °C until late winter–spring planting) and compared with seedlings lifted in March (stored above 0 °C until planting). Growth potential at the time of planting was measured by monitoring changes in root initiation, fresh weight, and root starch concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Poor field performance of cold stored plants has been attributed in part to strong reduction in NSC levels (Ritchie 1982, Table 5). However, few studies have found a close relationship between field performance and seedling NSC following storage (Puttonen 1986;Cannell et al 1990;Omi et al 1994). Similarly, seedlings exposed to prolonged drought stress either after spring shoot growth or when planted under deep shade, such as in the understory of forest stands, might also show severe reductions in tissue NSC levels (O'Brien et al 2014).…”
Section: New Forestsmentioning
confidence: 99%
“…Poor field performance of cold stored plants has been attributed in part to strong reduction in NSC levels (Ritchie 1982, Table 5). However, few studies have found a close relationship between field performance and seedling NSC following storage (Puttonen 1986;Cannell et al 1990;Omi et al 1994). Similarly, seedlings exposed to prolonged drought stress either after spring shoot growth or when planted under deep shade, such as in the understory of forest stands, might also show severe reductions in tissue NSC levels (O'Brien et al 2014).…”
Section: New Forestsmentioning
confidence: 99%